The Crucial Role of Plant Taxonomy in Ensuring the Biodiversity Sustainability: Insights from the Pharmaceutically Significant Genus Paris (Melanthiaceae) - Yunheng Ji; Zhiwei Yang; Xinqi Zhang; Shengji Pei (Taxonomy)
Taxonomy, primarily focused on systematically exploring, documenting, and characterizing global or regional biodiversity, represents a fundamental scientific discipline for biodiversity conservation and sustainability. However, it has encountered significant developmental constraints and academic marginalization in recent decades, resulting in a notable decline in proficient taxonomists as well as substantial gaps in taxonomic knowledge. In order to call for widespread attention and recognition of the increasing demands to revitalize and advance taxonomy, this article presents a comprehensive review that emphasizes the detrimental impacts of taxonomic knowledge gaps on the conservation and sustainable use of Paris (Melanthiaceae), a monocotyledonous genus hosting remarkable pharmaceutical significance and scientific importance. Overall, the conservation of threatened Paris species as well as the standardization of the cultivation of medicinal Paris species encounter numerous obstacles due to the scarcity of taxonomic expertise and presence of taxonomic knowledge gaps. These findings provide robust empirical evidence highlighting the crucial importance of taxonomy in biodiversity conservation and sustainability, thereby justifying the appeal to resurgence and advancement within this scientific discipline.